Strategy For Competitive MSMEs In Makassar City - Sain Segar K. Sid; Adrian Polim (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The COVID-19 epidemic has crippled all parts of society, particularly the economy. This predicament necessitates creative and effective survival techniques, particularly for operating a firm in the middle of an economic crisis. The purpose of this study is to investigate how MSMEs in Gaddong Village, Bontoala District, Makassar, apply creative techniques and solutions to mitigate the effects of the Covid-19 epidemic. This phenomenological investigation employs qualitative methods. Researchers purposefully chose research informants, and data was obtained via semi-structured interviews and focus group discussions. Following communicative, argumentative, and ecological validation, data were analyzed thematically using an inductive model. The study's findings indicate that themes like as optimism, self-control, confidence in one's own talents, and a willingness to undergo self-transformation are qualities that reveal the potential to live in the new normal. MSME players' survival strategies have two key focuses: product enhancement and company digitization.